2019
DOI: 10.1080/21679169.2018.1549594
|View full text |Cite
|
Sign up to set email alerts
|

Patient and healthcare worker safety risks and injuries. Learning from incident reporting

Abstract: Objectives: Learning from incident reporting systems is one core strategy to develop a culture of safety for healthcare workers and patients. The aim of this retrospective study was to explore patient injuries focussing on falls. Furthermore, on healthcare workers incidents, injuries and the situations they occurred. Method: A total of 65,749 patient risks and incidents were registered in the incident reporting system between 2011 and 2014. Of these, 11,006 were classified as an injury to a patient. Risks and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…The question about perceived sleep quality was scored on a 10-point scale [1][2][3][4][5][6][7][8][9][10], with a lower score reflecting better sleep. The factors demand for precision, work posture, psychosocial demands, social support, and items for leadership and perceived sleep were then dichotomised (1-5 and 6-10), with the values 1-5 indicating the positive aspects of exposure at work and presented as percentages.…”
Section: Physical and Psychosocial Workplace Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The question about perceived sleep quality was scored on a 10-point scale [1][2][3][4][5][6][7][8][9][10], with a lower score reflecting better sleep. The factors demand for precision, work posture, psychosocial demands, social support, and items for leadership and perceived sleep were then dichotomised (1-5 and 6-10), with the values 1-5 indicating the positive aspects of exposure at work and presented as percentages.…”
Section: Physical and Psychosocial Workplace Conditionsmentioning
confidence: 99%
“…There is consistent evidence that occupational health-related problems are prevalent among employees in dental organisations, and the risk of work related injuries is still a major concern [2,5]. A recent study reported the prevalence of injuries for both patients and employees in healthcare and dentistry indicating the need for prevention, assessments of risks, and tailored interventions at the workplace [6]. Work-related stress is reported to be prevalent also [2,7].…”
Section: Introductionmentioning
confidence: 99%
“…Threats and violence are in fact more frequently reported in Swedish health care than in other Swedish workplaces, and the percentage of those exposed has increased in the last years [6]. All of these exposures may lead to a variety of injuries such as musculoskeletal injury, wounds, infections or psychological symptoms [7,8]. The risk factors for occupational injury can be attributed to an interaction between characteristics of the worker and the patient, and the workplace [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…1 Systematic analyses of these reports is a good way to develop a safety culture in healthcare. 2 Although a single report does not necessarily lead to a change in healthcare systems, pooling and analysing reports can highlight gaps and faults in the environment. It is necessary to investigate what occurred and, why it occurred, and to determine the deficiencies in the system that allowed the incident to take place.…”
Section: Introductionmentioning
confidence: 99%